Effects of interfacial layer on thermal conductivity enhancement of solar salt-based nanofluids: Insights from molecular dynamics simulations - Zhenghua Rao; Rui Bai; Kai Ye; Tian Zhou (Case Studies in Thermal Engineering, 2022)
The interfacial nano-layers around the nanoparticles (NPs) affect the effective thermal conductivity (ETC) of molten salt-based nanofluids (MSBNFs), which brings challenge in fabricating MSBNFs with enhanced ETC. This paper presents insights into the interfacial layer and its effects on ETC of solar salt-based nanofluids through molecular dynamics simulation. The SiO2 and Al2O3 NPs with diameters of 1–2 nm and mass fractions of 0.5–2.0 wt% are considered. The results show that both the size and specie of NPs affect the thickness of the outer interfacial layer. The mass fraction has less significant effect on the thickness of interfacial layer, but is closely related to the degree of order in the interfacial layer. The ETC of MSBNFs varies with mass fraction and reaches the peak at a certain mass fraction. For MSBNFs with SiO2 NPs and Al2O3 NPs, the peak ETC occurs at mass fraction of 0.5 wt%, which increase by 3.5% and 7.0% at NP diameter of 1 nm respectively, and by 8.1% and 14.8% at NP diameter of 2 nm respectively. Detailed explanations to the physics of ETC enhancement of MSBNFs are presented in the view of interfacial layer from molecular level.